Factors influencing inadequate diagnosis and follow-up of leprosy reactions in Rondônia state, Brazil - Oliveira, Carmelita Ribeiro de (2007)
Leprosy reactions continue being one of the great challenges for National Leprosy Control Programs in endemic countries. The clinical aspects of reactions are well known, but data on the epidemiology are scanty. This hinders the elaboration of effective control strategies. In this study, factors were characterized which influenced inadequate diagnosis and follow-up of patients with leprosy reactions, as well as the impact of reactions on the development of physical disabilities. The descriptive operational study was done in Rondônia State in 1997, based on newly diagnosed cases and those that received discharge for cure. Data on leprosy reactions were obtained from medical records. Patients with reactions after discharge and progression of disability during treatment were interviewed, and a clinical evaluation was done. In addition, we described the structure of the Leprosy Control Programs in selected municipalities. Our data show that in Rondônia, despite progress in case detection, better availability of multidrug therapy, and reduction of disability grade at diagnosis and discharge from treatment, there continue to be difficulties in the management of leprosy reactions. Thus, it is necessary to define priorities focussing on the management of reactions, as a strategy to improve integrated patient care.